KEAMANAN STEVIA HASIL BUDIDAYA B2P2TO2T DALAM ASPEK TERATOGENITAS - Widowati, Lucie; Kusumadewi, Awal Prichatini; Murhandini, Sri (Badan Penelitian dan Pengembangan Kesehatan, 2011)
Teratogenic test has been performed on sweet stevia as product of B2P2TO2T cultivation at rats (Rattus novergicus) pregnant female Wistar. Stevia sweet was administered orally at a dose of 360, 120 and 40 mg/kg bw, volume 1 ml/100g bw per day during organogenesis period, on the day of pregnancy to the 6th until 15th. During the test, test animals were observed two times daily with the distance of six hours against the toxicity symptoms such as changes in skin, hair, eyes and mucous membranes, bleeding. Animals that experienced abortion, premature birth or death during the trial period were sacrificed and observed immediately with microscopic technic. At 20th day of pregnancy all of the pregnant rat dissected, and put out the fetuses from the mother's and observated the health conditions in general and the whole of mothers reproductive systems of fetuses, the outer fetal malformation and soft tissue system of fetal. The conclusion were sweet stevia of B2P2TO2T no worse effect on the mother rats, fetal body weight and morphology of mother rats and the fetus, does not affect the process of development of fetal soft tissue, and does not affect the development of fetal skeleton. Generally the B2P2TO2T stevia sweet substances safe for used, does not cause teratogenic effects.